ANTHROPOGENIC ACTIVITIES AND SUSTAINABILITY OF FOREST RESOURCES: CASE OF COMMUNITY FORESTS IN SIGLE/CENTRAL-WEST, BURKINA-FASO - Tiamiyu, Kasimou; Yanogo, Pawendkisgou Isidore (Floresta, 2024)
orest ecosystems from Burkina Faso are suffering from natural and anthropogenic disturbances that threaten their sustainability. This study aims to investigate human practices that pose a threat to the sustainability of community forests in the community of Siglé, in the Centre-West region of Burkina Faso. A mixed method (quantitative and qualitative), that consisted to survey questionnaires, interviews and field observations was employed. Ten practices that threaten the sustainability of forest resources were observed. The pFractices that pose the greatest threat to the forests were: i) Harvesting of fruits; ii) forest fires, expansion of the cultivation area and grazing, with average scores ranging from 2.59 to 3.5 on the Likert scale. These activities need to be regulated by the community authorities for the harmonious development of forest spaces in the municipality.